A thermal-electrical-mechanical coupling framework solving the deformation characterized by extreme adiabatic heating and geometric non-uniformity - H.C. Sun; J.S. Yan; S. Yang; Y. Li; L.L. Zhu; H. Zhang; N. Ueshima; Y.X. Liu; K. Oikawa; L. Jiang; J.J. Ruan (Journal of Materials Research and Technology, 2025)
High-strength powder metallurgy superalloys often suffer from deformation non-uniformity, cracking, and adiabatic heating during thermomechanical processing. Traditional constitutive models, reliant on friction/adiabatic corrections, fail to address challenges, such as geometric deformation heterogeneity (dead metal zone) and large temperature gradients during hot deformation. This study establishes a thermal-electrical-mechanical coupling framework using MATLAB-DEFORM co-simulation to solve the Norton-Hoff constitutive parameters by minimizing deviations between simulated and experimental load-temperature data. The stress-strain responses, temperature profiles, and geometric evolution during compression tests using the Gleeble 3500 system were recorded for the simulation. The coupled framework achieved high accuracy, with simulated load-stroke curves aligning closely with experimental data (<10 % error) and temperature control within ±2 °C of targets. Strain-dependent parameter optimization revealed thermal activation term, β, as the dominant variable, increasing from 61100 to 61595 K. Meanwhile, microstructural analysis demonstrated minimal grain size change (2.61 → 2.54 μm) but an increment in coarse γ′ phase area (31 %→41 %). The increment in γ′ phase amount leads to a Cr/Mo/W refractory element redistribution into the matrix during deformation, validating the positive strain-dependent β value and offering insights into unconventional deformation mechanisms. Unlike the influence of dislocation on DRX process reported in many alloys, the dislocation formed during deformation here was discovered to pile up at γ/γ′ boundaries and undergo annihilation. This study provides a pioneering methodology for constitutive modeling in high-strength superalloys, addressing geometric and thermal heterogeneities through integrated simulation-experimental validation.